Information Literacy and Research Development Skills: Advancing Librarian’s Participation in Pedagogical Research - Yoshida, Asako (Qualitative and Quantitative Methods in Libraries; Vol 3 No 4 (2014): December 2014 Issue, 2017)
Information literacy continues to be an important professional agenda conceptualizing and advancing academic librarians’ teaching roles for the 21st century.  In this paper, the author advances librarians’ proactive involvement in the Scholarship of Teaching and Learning (SoLT) as an alternative and potentially effective avenue to enhance teaching and learning of research skills on campuses.  She will draw her pedagogical research stance from the experiences of undertaking: 1) a blended learning project involving two different 2nd year undergraduate foundational courses in the Faculty of Human Ecology, and 2) a pedagogical research project for a 4th year research seminar course in the Department of Human Nutritional Sciences.  Qualitative and quantitative methods are used to explore student learning in both projects.  The blended learning project was restricted to research paper assignment aspects in the courses.  In contrast, the second project will look at the entire course and its effectiveness in facilitating student learning and engagement in research. The author concludes that librarians can find new ways of contributing to enhancing student learning and engagement in research by capitalizing on their involvement in SoLT to advance student learning, the common interest of both teaching faculty and librarians, rather than keeping their information literacy educational efforts in 'the library silo'.